Morphometric growth characteristics and body composition of bullfrog tadpoles in captivity - Menegasso Mansano, Cleber Fernando [UNESP]; De Stéfani, Marta Verardino [UNESP]; Pereira, Marcelo Maia [UNESP]; Ribeiro Nascimento, Thálita Stefann [UNESP]; Macente, Beatrice Ingrid [UNESP] (Univ Estadual Londrina, 2014)
Feed management needs to be improved in frog farming to reduce the indirect effects of inadequate feeding and, consequently, to increase growth rates and nutrient deposition, obtaining better quality animals. The objective of this study was to establish morphometric growth curves for bullfrog tadpoles (Lithobates catesbeianus) and to determine nutrient deposition in the carcass. A total of 6,480 bullfrogs (Gosner stage 25) received an experimental diet (26.23% digestible protein and 32.68% crude protein) and a commercial diet (37.92% crude protein) ad libitum. A Gompertz model was used to describe the growth curve. Tadpoles fed the experimental diet presented higher final protein deposition. In addition, the sigmoidal curve was much more homogenous, indicating a more constant daily protein deposition rate. The Gompertz model provided an excellent fit of the data to describe the morphometric growth curve and carcass nutrient deposition of bullfrog tadpoles, showing that animals fed the experimental diet presented a better growth rate and nutrient deposition.

Melhorias no manejo alimentar devem ser implementadas na ranicultura, visando diminuir os efeitos indiretos da alimentação inadequada, resultando em melhores taxas de crescimento e deposição de nutrientes, consequentemente obtendo animais de melhor qualidade. O objetivo foi estabelecer curvas de crescimento morfométrico de girinos de rã-touro e sua deposição de nutrientes na carcaça. Foram utilizados 6.480 girinos de rã-touro no estágio 25 de Gosner, alimentados com dieta experimental (26,23% PD e 32,68% PB) e comercial (37,92% PB), oferecida ad libitum. O modelo utilizado para descrever a curva de crescimento foi de Gompertz. Os girinos alimentados com a dieta experimental, além de apresentarem uma deposição protéica final maior, o modelo sigmoidal apresentou-se muito mais homogêneo, mostrando uma taxa de deposição protéica diária mais constante. O modelo de Gompertz apresentou um ótimo ajuste para descrição da curva de crescimento morfométrico e deposição de nutrientes na carcaça para girinos de rã-touro, mostrando que os girinos alimentados com a dieta experimental, apresentaram melhor taxa de crescimento e deposição de nutrientes na carcaça.
Características do crescimento morfométrico e composição corporal de girinos de rã-touro em cativeiro
Keywords: Frog farming; Gompertz model; growth curve; nutrient deposition; Ranicultura; Modelo de Gompertz; Curva de crescimento; Deposição de nutrientes